Prostacyclin pathway vasodilators in patients with chronic thromboembolic pulmonary hypertension (CTEPH): A systemic review and meta‐analysis of randomized controlled trials - Weijun Li; Xingxue Pang; Jun Chen; Xiaoxia Ren; Huaibing Zhao; Xu Wang; Ning Zhao; Dayi Hu; Zhongyi Jin (Pulmonary Circulation)
Abstract Although surgical and interventional therapy has emerged as the primary treatment for patients with chronic thromboembolic pulmonary hypertension (CTEPH), there remains a subset of patients who need medication therapy. This study aimed to evaluate the efficacy and safety outcomes of prostacyclin pathway vasodilators, providing further insight for clinical decision‐making. A literature search was conducted in PubMed, Embase, and CENTRAL databases from inception to December 2023. Literature screening and quality assessment were carried out with the Cochrane Risk of Bias Tool. Data analysis was conducted using RevMan 5.4 software. We included 6 randomized controlled trials with 387 patients. Prostacyclin pathway vasodilators demonstrated a significant improvement in PVR (−125.26 dynes·sec·cm−5, 95%CI: −219.29 to −31.23, Z = 2.61, and p < 0.009), RAP (−0.78 mmHg, 95%CI: −1.52 to −0.04, Z = 2.06, and p = 0.04), cardiac index (0.62, 95%CI: 0.54 to 0.69, Z = 16.13, and p < 0.00001), and the number of patients showing improvement in WHO functional class (3.86, 95%CI: 1,92 to 7.77, Z = 3.79, and p = 0.0002) compared to controls, moreover, a trend towards improvement was observed in mPAP, 6MWD, and NT‐proBNP. Regarding the safety endpoints, no significant difference was found in both groups in terms of serious adverse events and all‐cause deaths. The prostacyclin pathway vasodilators present therapeutic potential for CTEPH patients with inoperable or persistent/recurrent PH after PEA/BPA primarily characterized by distal small‐vessel and microvasculopathy. However, the current clinical evidence remains insufficient and controversial, necessitating further validation.